Mature Cystic Teratoma Mimicking Ectopic Pregnancy in A Patient with Spontaneous Abortion: A Case Report - Özlem Moraloğlu; Seçil Günaydın Özban; Özlem Altınkaya; Ümit Bilge (Medical Network, 2009)
A case of mature cystic teratoma mimicking ectopic pregnancy in a patient with positive serum β-hCG and adnexal mass is presented. A 25 year-old woman referred to emergency clinic with pelvic pain and vaginal bleeding with passage of blood clots. β-hCG level was 1618 IU/L. Ultrasonography revealed a heterogeneous adnexal mass 63x42 mm in size and absence of intrauterine gestational sac. Based on these findings, a diagnosis of ectopic pregnancy was suspected. At laparoscopy, mature cystic teratoma was discovered. The patient was treated with cyst removal. Certain diagnosis was proved to be mature cystic teratoma simultaneously occurring with spontaneous abortion, mimicking ectopic pregnancy. Although the presence of an adnexal mass in the absence of an intrauterine gestational sac with positive β-hCG level above the threshold level, may indicate an ectopic pregnancy; differential diagnosis of mature cystic teratoma simultaneously occurring with spontaneous abortion should be kept in mind.